Early Childhood Literacy Teachers in High Poverty Schools : a Study of Courage and Caring. - Landa, Melissa (Lexington Books, 2017)
This book analyzes white early literacy teachers' experiences in low-income school communities. Through in-depth interviews that excavate the teachers' sense of identity and their life experiences, Landa blends their successful practices with theoretical frameworks about teaching low-income children of color.